2009
DOI: 10.1177/0894486509332327
|View full text |Cite
|
Sign up to set email alerts
|

Family Social Capital, Venture Preparedness, and Start-Up Decisions

Abstract: Using insights from the resource-based view, social capital, and network theories, the authors develop a model of how family social capital, as well as an entrepreneur’s knowledge capital and external social capital, influences the venture creation process. The model is tested on a sample of 85 nascent Hispanic entrepreneurs. Results indicate that family social capital, measured as family support, contributes to venture preparedness and the start-up decision, suggesting that it has both a direct and an indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
150
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(162 citation statements)
references
References 91 publications
(172 reference statements)
5
150
0
3
Order By: Relevance
“…Increasing family size, geographical distribution, and ownership dispersion usually coming along with generational transition (Schulze et al 2003) could give strong incentives to pursue international entrepreneurship opportunities. In a similar vein, research on ethnic entrepreneurship (Chang et al 2009;Light and Bonacich 1988;Light and Gold 2000) has found that ethnic entrepreneurs pursue other, non-financial goals when internationalizing their businesses, such as maintaining relationships with relatives in their home countries. Hence, immigration status, ethnical background, kinship ties in the country of origin, as well as the number of generations owning the business and ownership dispersion could be important drivers behind the decision to take the family business international.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Increasing family size, geographical distribution, and ownership dispersion usually coming along with generational transition (Schulze et al 2003) could give strong incentives to pursue international entrepreneurship opportunities. In a similar vein, research on ethnic entrepreneurship (Chang et al 2009;Light and Bonacich 1988;Light and Gold 2000) has found that ethnic entrepreneurs pursue other, non-financial goals when internationalizing their businesses, such as maintaining relationships with relatives in their home countries. Hence, immigration status, ethnical background, kinship ties in the country of origin, as well as the number of generations owning the business and ownership dispersion could be important drivers behind the decision to take the family business international.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…However, studies that have addressed these factors have only studied family firms, and usually study the effect these factors can have on incentives to mitigate agency problems. For example, authors have shown variations in that relationship when introducing mediating variables, as is the case when considering the generation in control [30,42,43], family management involvement [37,44,45], provision of incentives [46], and when distinguishing between lone-founder and family firms [43,47]. Thus, it is increasingly important to study the way in which these factors function in order to discover the nuances that make them successful for family firms and unsuccessful for non-family firms, and vice versa.…”
Section: Effect Of Other Factors On Performancementioning
confidence: 99%
“…Family and relatives, friends and social networks' peers are an integral part of the game (Chang, Memili, Chrisman, Kellermanns, & Chua, 2009;Zahra, Hayton, Neubaum, Dibrell & Craig, 2008) as the social relationship offers further legitimacy to new venture (Meyer & Rowan, 1977;Hannan & Freeman, 1984;Nagy, Pollack, Rutherford, & Lohrke, 2012). The emerging trend of crowdfunding further emphasizes of the traditional factors (Brown, 1993;Mollick, 2014) most probably due the fact that entrepreneurs and new ventures will likely in need of presenting their credentials to gradually gain credibility (Hannan & Freeman, 1984).…”
Section: A Brief Literature Reviewmentioning
confidence: 99%